Humectability and Physical Properties of Hydroxypropyl Methylcellulose Coatings with Liposome-Cellulose Nanofibers: Food Application - Osorio-Lira, F; Zamorano-Riquelme, M; Silva-Weiss, A; Lopez-Polo, J (Elsevier Ltd, 2020)
The objective of this study was to investigate the physical, rheological and humectability properties of edible coating forming suspensions (ECS) based on hydroxypropyl methylcellulose (HPMC) containing: liposomes that encapsulate rutin, glycerol and cellulose nanofibers on sliced surfaces of almonds and chocolate. On average, liposomes measured between 110.6 ± 10.0 nm and were characterized as stable and homogeneous suspensions. Adding these liposomes to the edible coatings produced significant changes (p< 0.05) in the density and surface tension, which favor the final appearance of the coating. The presence of liposomes increased the apparent viscosity of the ECS, showing a purely viscous and fluid behavior with a good fit (R2 = 0.9996) with the Power Law model. The presence of liposomes and cellulose nanofibers decreased the value of the cohesive energy of the ECS. The studied ECS partially hydrate the surfaces of almond and chocolate as they showed contact angles under 90°. © 2019 Elsevier Ltd